Ketahanan Padi Transgenik Db1 Terhadap Wereng Coklat (Nilaparvata lugens Stal.) Biotipe 3 (Resistance of Db1 Transgenic Rice to Biotype 3 of Brown Planthopper (Nilaparvata lugens Stal.) - Nono Carsono; santika sari; danar dono; kinya toriyama (Breeding Science Society of Indonesia (BSSI) / PERIPI, 2019)
Brown planthopper has been recognized as a primary pest of rice in Indonesia and most Asian countries. Developing rice lines resistant to this pathogen is an effective and environmentally friendly approach. Rice cv. Taichung 65 has been transferred with Db1 gene from yam tuber Dioscorea batatas, to improve its resistance to insect pathogen. The rice plant, however, is not been known yet of its resistance to biotype 3 of brown planthopper from Indonesia. The objective was to obtain resistance level of Db1 transgenic rice against biotype 3, the brownest planthopper attacking rice. The experiment was arranged in randomized block design, and some tests performed were screening resistance, honeydew test, and the oviposition preference. Results indicated that Db1 Taichung transgenic rice had improved resistance level as compared to its wild type; from very susceptible to susceptible. Db1 transgenic rice line had a lower resistance level compared to those of cv. PTB33, Rathu Heenati, Ciherang, Babawee, IR64, dan Cisadane. It could be seen from a higher amount of honeydew excreted and a number of an egg laid by brown planthopper compared to those of tested cultivars. It is concluded that DB1 transgenic line is susceptible, then it is not sufficient to control brown planthopper specifically biotype 3.